Simultaneous Optical Performance Monitoring and Modulation Format/Bit-Rate Identification Using Principal Component Analysis - Tan, Ming Chieng; Khan, Faisal Nadeem; Al-Arashi, Waled Hussein; Zhou, Yudi; Lau, Alan Pak Tao (IEEE, 2014)
We propose a novel technique for simultaneous multi-impairment monitoring and autonomous bit-rate and modulation format identification (BR-MFI) in next-generation heterogeneous fiber-optic communication networks by using principal component analysis-based pattern recognition on asynchronous delay-tap plots. The results of numerical simulations performed for three commonly used modulation formats at two different bit-rates each demonstrate simultaneous and independent monitoring of optical signal-to-noise ratio, chromatic dispersion, and differential group delay with mean errors of 1 dB, 4 ps/nm, and 1.6 ps, respectively, without knowing the signal's bit-rate and modulation format. Similarly, the results for joint BR-MFI validate accurate identification of all the bit-rates and modulation formats despite the presence of various network impairments. The effects of fiber nonli-nearity and transmitter variations on the performance of the proposed technique are also investigated.